Nursing Care for Mr. A with Hyperglycemia and the Implementation of Progressive Muscle Relaxation in the Emergency Room at Hermina Jatinegara Hospital, Jakarta: A Case Report - Dea Arista; Emmi Wahyuni; Lutfiasih Rahmawati (Ammar Dharma Foundation, 2024)
Background: During Hyperglycemia is a condition where blood sugar levels are higher than normal levels, which is less than 200 mg/dl for casual plasma glucose values. Uncontrolled hyperglycemia can cause blood sugar levels to spike so high that it can cause emergency hyperglycemia.Objective: This study aims to determine the description of nursing care for patients with hyperglycemia with progressive muscle relaxation intervention.Research Method: This type of research is a case report. Data collection for this case study was carried out in the Emergency Room of Hermina Jatinegara Hospital on October 11, 2023. Data collection was carried out through observation, physical examination, and interview methods. Diagnostic examination data were obtained through the results of medical record records. Blood glucose levels were measured using a Glucometer.Results: Mr. A, 41 years old, male with a medical diagnosis of hyperglycemia, the results of the assessment were found that the client complained of weakness, dizziness, often felt thirsty, had nausea and vomiting 2 times and had 5 loose stools since morning, the extremities felt cold, skin turgor decreased and dry, bowel sounds frequency 40x / minute, blood glucose levels were 432 mg / dl, leukocyte levels were 14.7 10¬ ^ 3 / µL, and hematocrit was 47%. The nursing diagnoses that were established were unstable blood glucose levels, hypovolemia, and diarrhea. The nursing interventions provided were hyperglycemia management and additional progressive muscle relaxation therapy, hypovolemia management, and diarrhea management. Nursing evaluation found that the problem of unstable blood sugar levels was resolved, the problem of hypovolemia was partially resolved, and the problem of diarrhea was partially resolved.Conclusion: This case report provides an overview of nursing care for patients with hyperglycemia and information on the effectiveness of providing additional interventions, namely progressive muscle relaxation.